Exploring the antimicrobial, antiviral, antioxidant, and antitumor potentials of marine Streptomyces tunisiensis W4MT573222 pigment isolated from Abu-Qir sediments, Egypt - Walaa M. Ibrahim; Zakia A. Olama; G. M. Abou-elela; Heba S. Ramadan; Ghada E. Hegazy; Dalia El S. El Badan (Microbial Cell Factories, 2023)
Abstract Due to the therapeutic importance of microbial pigments, these pigments are receiving the attention of researchers. In this present study 60 isolates were isolated from sediments of Abu-Qir coast of the Mediterranean sea, Alexandria, Egypt, out of which 12 were considered as pigmented actinomycetes. Streptomyces sp. W4 was characterized by small round green pigmented colonies when grown on starch-casein agar medium. The green pigment was extracted using a mixture of acetone-methanol (7:3 v/v). The antimicrobial, antioxidant, antiviral, and anticancer activities of the green pigment produced by Streptomyces sp.W4 were investigated. The pigment was characterized using FTIR, Raman spectroscopy, EDX and GC–MS. The results revealed that the pigment has antibacterial and antifungal activity and also showed inhibition of HAV 78% but its antiviral activity against the Adenovirus was weak. The results proved the safety of the pigment toward normal cells and anticancer activity against three different cancer cell lines HepG-2 (liver cancer cell line), A549 (lung cancer cell line), and PAN1 (pancreas cancer cell line). The pigment was combined with 9 antibiotics and then tested against the Gram-negative bacterium Enterococcus faecalis using disc diffusion bioassay. LEV showed an antagonistic effect, while CXM and CIP showed a synergistic effect.